Evaluation of Business Model Development through Customer Discovery Approach (Case Study of PT Hijup.com) - Teti Hariyati (Tazkia Islamic Finance and Business Review, 2016)
Objectives: Islamic fashion e-commerce grows rapidly in Indonesia. Hijup.com is the pioneer and the biggest player in the industry. In order to thrive in fiercer competition, Hijup.com needs to improve its business model. The study aims to seek a more suitable business model for Hijup.com using customer development approach.Method: The research used action research strategy. Starting by mapping current businesss model, the research tested the model to customer, revised the business model, and tested back to the customer.  The data was collected through an in-depth interview to 60 customers.Result: The results found that the customers had problems with the user-friendliness of website, product variation, uninformative private shopping, payment methods, and pricing.  These problems were not answered yet by the available product and services offered.  It was also found that there was neglected customer segment: university students. As response to the problems, the solutions were designed by improving the web with mobile appstore, chat online, layout hot items, adding product variations, credit card promotion, adding new stocks for student segments.Conclusion: Having tested the solutions to the customers, the majority of them accepted the improvement although there were some minor improvements needed. Based on the new solutions, the new business model for Hijup.com was created.